Changes in Serum, Red Blood Cell, and Colonic Fatty Acids in a Personalized Omega-3 Fatty Acid Supplementation Trial. (7th February 2022) - Shen, Yifan; Sen, Ananda; Turgeon, D. Kim; Ren, Jianwei; Graifman, Gillian; Ruffin, Mack T.; Smith, William L.; Brenner, Dean E.; Djuric, Zora
Abstract: This study evaluated changes in fatty acids from sera, red blood cells, and colonic biopsies from a phase Ib clinical trial of personalized ω-3 fatty acid dosing in 47 healthy volunteers. The trial aimed to reduce colonic prostaglandin E2 (PGE2 ), a pro-inflammatory product of arachidonic acid (AA) oxidation. The personalized doses ranged 2–10 grams/day (54% eicosapentaenoic acid, EPA, 24% other ω-3 fatty acids). In colon, increases in ω-3 highly unsaturated fatty acids (HUFA) and EPA:AA ratios each were correlated with decreases in PGE2 . Changes in either colonic EPA:AA ratios or ω-3 HUFA were significantly correlated with changes in the same fatty acid measures in red blood cells or serum. The only blood-based measure significantly correlated with changes in colonic PGE2 was change in red blood cell ω-3 HUFA (ρ = −0.39), and the increase in red blood cell ω-3 HUFA was significantly greater in participants who had at least a median reduction in colonic PGE2 vs. those who did not. In summary, fatty acid changes in blood did reflect fatty acid changes in the colon, but additional factors will be needed for optimizing dosing models that seek to predict the anti-inflammatory effects of ω-3 fatty acids on the colon.